Prolonged low-dose thrombolysis in posterior circulation stroke - Hametner, Christian; Kellert, Lars; Veltkamp, Roland; Behrens, Lars; Nagel, Simon; Hacke, Werner; Ringleb, Peter A. (Neurocritical care, 2014)
We aimed to investigate the feasibility, preliminary safety, and efficacy of prolonged low-dose intravenous thrombolysis in posterior circulation stroke patients with a thrombus lodged in the basilar artery who were ineligible for standard rtPA administration.
Published online: 19 November 2013
Gesehen am 13.10.2021